2000
DOI: 10.1074/jbc.m907862199
|View full text |Cite
|
Sign up to set email alerts
|

Identity of Urinary Trypsin Inhibitor-binding Protein to Link Protein

Abstract: Urinary trypsin inhibitor (UTI), a Kunitz-type protease inhibitor, directly binds to some types of cells via cell-associated UTI-binding proteins (UTI-BPs Urinary trypsin inhibitor (UTI)1 is a Kunitz-type protease inhibitor that is responsible for the inhibition of several proteases in serum and urine as well as in amniotic fluid (1). We (2-4) and others (5, 6) have found that UTI can directly bind to neoplastic cells as well as to non-neoplastic cells via cell-associated UTI-binding proteins (UTI-BPs) or spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
50
0
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 49 publications
0
50
0
1
Order By: Relevance
“…The differences in bikunin sensitivity could be the result of variability in drug metabolism, a higher dependence on calciumsensitive functions for cell invasiveness in certain types of cells, or a variability of the amounts of bikunin receptors on tumor cell membrane (37,38). There appeared to be a specific interaction between bikunin and the tumor cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in bikunin sensitivity could be the result of variability in drug metabolism, a higher dependence on calciumsensitive functions for cell invasiveness in certain types of cells, or a variability of the amounts of bikunin receptors on tumor cell membrane (37,38). There appeared to be a specific interaction between bikunin and the tumor cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…2 Furthermore, we showed that there is a direct correlation between bikunin overexpression and the reduced metastatic potential of primary tumor biopsies (12) and tumor cell lines as reflected by their in vitro potential to invade through a Matrigel TM barrier. 2 We have shown that bikunin is part of the negative invasive program as evaluated by their invasion and uPA/uPAR synthesis (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…We have established that LP can interact with the NH 2 -terminal domain of bik, while bik-R is able to recognize the C4S side chain of bik (15,17). Analysis of binding of native bik and deglycosylated bik to the cells showed that the low affinity binding site is LP and the high affinity site is bik-R (17).…”
mentioning
confidence: 99%
“…To more precisely map the regions in the bik that can interact with LP and bik-R, various truncated proteins were tested in the solid-phase binding and ligand blot assays (15,17). We have established that LP can interact with the NH 2 -terminal domain of bik, while bik-R is able to recognize the C4S side chain of bik (15,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation